STRUCTURAL PATTERNS OF PRE-URALIDES IN THE ENGANEPE UPLIFT (POLAR URALS) AS A REFLECTION OF THE CAMBRIAN COLLISION OF BALTICA AND ARCTIDA - Kuznetsov N.B.; Kulikova K.V.; Udoratina O.V. (My University, 2007)
The East European Platform (EEP) is bordered by the Ural foldbelt of Hercynides on the east and the Pechora Plate (PP) with the adjacent Barents Sea shelf in the northeast. The upper horizons of the Earth’s crust in the Urals, PP, and Barents shelf are characterized by a two-level structure. The lower stratigraphic–structural level consists of Late Precambrian complexes (Pre-Uralides–Timanides), whereas the upper level is composed of Postcambrian complexes.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская